'We're meat, so we need to eat meat to be who we are': Understanding motivations that increase or reduce meat consumption among emerging adults in the University of Ghana food environment. (November 2022) - Mensah, Daniel Opoku; Mintah, Faustina Ofosua; Oteng, Sylvia Adoma; Lillywhite, Rob; Oyebode, Oyinlola
Abstract: The increasing presence of meat products in the diets of sub-Saharan African (SSA) populations have consequences for human and planetary health in the subregion. But there are questions about whether emerging adults in SSA setting who are both important targets and potentially key drivers of dietary change are willing to modify their diets for health and ecological benefits. This study used focus group discussions and best friend dyad interviews with 46 university students. Verbatim transcripts were analysed thematically using NVivo-12. Various motivations to increase or reduce meat consumption are highlighted by the results, some of which participants deemed more relevant than others. Health concerns; animal welfare; and environmental sustainability were not important to this age group, and they did not consider changing their behaviour based on these drivers. Body weight/shape, meat as identity, pleasure, and joy; and meat-eating as part of socialisation were frequent drivers of increased meat consumption; religion/cultural practices were frequent drivers of limited consumption.